Translating Toshiko Ellis and its Challenges as a Woman Translator - Sepúlveda Aguilar , Izabella (2022)
This article analyzes the translation of the article "Woman and the Body in Modern Japanese Poetry" by Professor Toshiko Ellis. The objective of it is to bring to light Japanese women´s feminine literature seen through the eyes and in the words of the author Toshiko. The most important contribution that is intended with this article and translation is to open the Spanish-speaking public's eyes and attention to Japanese women's poetry, since there is no other translation made, known or published of the work of the Japanese writer in Spanish. Therefore, with this first contribution, by translating the text, it is hoped that our society and readers will better understand this ancient culture and identify with its words, feelings, struggles, joys and sorrows.